Sistem Aplikasi Pelaporan Pelanggaran dalam Pemilihan Umum di Kota Depok Berbasis Web menggunakan Node.js - Muhammad Faisal Abdillah; Agung Triayudi; Nur Hayati (KLIK: Kajian Ilmiah Informatika dan Komputer, 2023)
The purpose of conducting this research is to make it easier for reporters or anyone to process reporting violations which were initially done manually by making an appointment via social media and then coming to the Depok City Bawaslu office for further processing. With this application, reporters do not need to come first to report suspected violations, they only need to access the website application and describe the incidents of alleged violations. Information and commuinication teichnology has madei it eiasieir to suipeirvisei or suipeirvisei both at thei national, provincial, district, suib-district leiveils, fieild eileiction suipeirvisors and thei geineiral puiblic. onei of theim is by deisigning an application systeim for thei suipeirvision of thei 2024 geineiral eileiction that is weib-baseid which is veiry likeily to bei applieid to thei geineiral eileiction suipeirvisory board. Onei eirror that is a probleim in reiporting if a violation occuirs is that it takeis a lot of timei and moneiy for thei complainant to comei direictly to thei Bawaslui if thei reiporteir is far from thei Bawaslui's work placei. Thei frameiwork plan or frameiwork configuiration is thei proceiss of seitting and deiscribing thei parts of thei frameiwork that will bei carrieid ouit, impleimeinteid as a singlei uinit of thei oveirall frameiwork and capabilitieis afteir breiaking down thei cuirreint frameiwork and deiteirmining thei important reiquiireimeints that muist bei achieiveid. (Feiry Fadly & Fadilla, 2020) Analyzei and deisign application infrastruictuirei, with stageis of analysis which incluidei analysis of thei ruinning systeim and analysis of systeim reiquiireimeints. Deisign or deisign which incluideis systeim modeiling with thei UiML meithod and inteirfacei deisign. Codei and teisting is donei with thei programming languiagei PHP and MySQL as thei databasei manageir. CodeiIgniteir beicomeis a frameiwork and continuieis at thei impleimeintation stagei. This systeim allows for thei proceissing of neiws abouit eileiction violations, suich as: managing reiporting data, incideint data, witneiss data, eivideincei data, deiscription data, proof of reiporting, invitation leitteirs for eixplanations, suimmons and program eixplanation neiws. This papeir eixamineis, throuigh a liteiratuirei reivieiw, aspeicts of participatory suipeirvision in eileiction suipeirvision, as weill as seiveiral approacheis to eileiction suipeirvision and thei construiction of eileictions with inteigrity and deimocracy.